Understanding Customer Value in the Mobile Internet Era - Jing Li; Ayenew Darge Nigatu; Baoquan Yu; Qiaolun Gu; Yong Yang (Discrete Dynamics in Nature and Society)
The advent of mobile Internet era brings both opportunities and challenges to understanding customer value in the field of customer relationship management. Traditional customer relationship management theory and practice focus on the transaction value created by individual customers and do not take into consideration enough to the huge potential commercial value behind the interaction and connection among people by means of online social services in the mobile Internet era. Towards this end, this study first analyses the new characteristics of customer behaviour in the mobile Internet era. Second, the study proposes the integrated customer value model in three dimensions of purchase value, interactive value, and marketing diffusion value with 13 indicators based on the complex network theory and RFM model, considering the value created by connection and interaction among customers. Finally, the study discusses the eight types of customer clusters and the corresponding differentiate customer relationship management strategies in the era of mobile Internet based on the integrated customer value model. This study enriches the theory of customer value in the field of customer relationship management and also helps company better practice the innovation and change in the management of relationship with customer in the mobile Internet era.